Tacrolimus Improves the Implantation Rate in Patients with Elevated Th1/2 Helper Cell Ratio and Repeated Implantation Failure (RIF) - Bahrami-Asl, Zahra; Farzadi, Laya; Fattahi, Amir; Yousefi, Mehdi; Quinonero, Alicia; Hakimi, Parvin; Latifi, Zeinab; Nejabati, Hamid Reza; Ghasemnejad, Tohid; Sadigh, Aydin Raei; Heidari, Mohammad Hassan; Nouri, Mohammad; Novin, Marefat Ghaffari; Dominguez, Francisco (Geburtshilfe und Frauenheilkunde, 2020)
Introduction An abnormal endometrial immune response is involved in the pathogenesis of repeated implantation failure (RIF), so we investigated the effectiveness of tacrolimus treatment on the endometrium of RIF patients.Materials and Methods Ten RIF patients with elevated T-helper 1/T-helper 2 (Th1/Th2) cell ratios were recruited into a clinical study. The expression of p53, leukemia inhibitory factor (LIF), interleukin (IL)-4, IL-10, IL-17, and interferon gamma (IFN-γ) in the endometrium of patients with and without tacrolimus treatment and the association of these factors with assisted reproductive technology (ART) outcomes were investigated.Results Tacrolimus significantly increased the expression of LIF, IL-10, and IL-17 and decreased the expression of IL-4, IFN-γ, and the IFN-γ/IL-10 ratio in RIF patients. Tacrolimus treatment resulted in an implantation rate of 40%, a clinical pregnancy rate of 50%, and a live birth rate of 35% in RIF patients with elevated Th1/Th2 ratios who had previously failed to become pregnant despite at least three transfers of embryos. We also found a significant positive correlation between IL-10 levels and the implantation rate.Conclusions Our findings suggest that RIF patients with a higher Th1/Th2 ratio could be candidates for tacrolimus therapy and that this immunosuppressive drug could be acting through upregulation of LIF, IL-10, and IL-17.
Keywords: repeated implantation failure; embryo implantation; tacrolimus; immune system; assisted reproductive technology (ART); intracytoplasmic sperm injection (ICSI); in vitro fertilization (IVF); leukemia inhibitory factor (LIF); interleukin (IL)-4, IL-10, IL-17; interferon gamma (IFN-γ)